2011
DOI: 10.1002/ijc.25456
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin‐β receptor activation by lymphotoxin‐α1β2 and LIGHT promotes tumor growth in an NFκB‐dependent manner

Abstract: Lymphotoxin beta receptor (LTβR) activation on mouse fibrosarcoma cells (BFS‐1) results in enhanced solid tumor growth paralleled by increased angiogenesis induced by the expression of pro‐angiogenic CXCL2. In our study, we demonstrate that both functional ligands of the LTβR, namely LTα1β2 and LIGHT, are involved in the activation of LTβR in solid fibrosarcomas. To identify whether the lymphocyte population is involved in the activation of LTβR in these fibrosarcoma tumors, we used conditional LTβ‐deficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…TNFα is deemed consistently to stimulate NFκB activation in different cancer cells. LT-α1β2 is also well known to stimulate NFκB activation in most cells [54-56]. Interestingly, we found that IL-1β, a common stimulator for NFκB signaling in most cells, fails to activate NFκB in MDA-MB-231 cells other than in HCT116 cells.…”
Section: Discussionmentioning
confidence: 69%
“…TNFα is deemed consistently to stimulate NFκB activation in different cancer cells. LT-α1β2 is also well known to stimulate NFκB activation in most cells [54-56]. Interestingly, we found that IL-1β, a common stimulator for NFκB signaling in most cells, fails to activate NFκB in MDA-MB-231 cells other than in HCT116 cells.…”
Section: Discussionmentioning
confidence: 69%
“…In further studies, it was shown that LTβR ligands LT and LIGHT expressed by tumor infiltrating lymphocytes lead to upregulation of the proangiogenic chemokine CXCL-2 in fibrosarcoma cells [100]. Therefore, LT also plays a tumor-intrinsic role for organization of tumor tissue during tumor development.…”
Section: Novel Effects Of Lt-mediated Signaling In Cancer Promotion Amentioning
confidence: 99%
“…The TNFR1:Ig, the mBD14:Ig, and the LTbR:Ig expression constructs were generated by insertion of the corresponding cDNA encoding for the extracellular domain of the TNFR1, the mature mBD14, or the soluble form of the LTbR into the Signal pIg plus vector (R&D Systems, WiesbadenNordenstadt, Germany), as described earlier (8,16,17). Stable transfectants expressing the TNFR1:Ig, the mBD14:Ig, or the LTbR:Ig fusion protein were prepared by transfection of BFS-1 cells with the corresponding expression construct using DOTAP (Roche Diagnostics, Mannheim, Germany), following the manufacturer's instructions.…”
Section: Dna Constructs and Transfectionmentioning
confidence: 99%
“…In earlier studies, we have shown that LTbR activation on BFS-1 tumor cells by ligand-expressing cells like activated B cells is a prerequisite for CXCL2 expression in BFS-1 tumor cells and subsequently tumor growth (17). Thus, we used the soluble LTbR:Ig fusion protein as inhibitor for LTbR activation.…”
Section: Inhibition Of Ltbr Activation Reduces the Enhanced Mbd14-depmentioning
confidence: 99%
See 1 more Smart Citation